Auctioning Concessions for Private Roads - Barry Ubbels; Erik Verhoef (Tinbergen Institute, 2004)
Private toll roads are now seriously considered as an alternative to public (free-access) road infrastructure. Nevertheless, complete private provision without governmental control is only rarely considered. A main consideration against private roads would be that operators would be primarily interested in maximizing profits, which – given the market power they will have – will typically not lead to welfare maximizing tolls and capacities. An important question is whether these discrepancies can be mitigated by a proper design of auctions for concessions of private roads. This paper therefore analyses capacity choice and toll setting by private investors in a competitive bidding framework organised by the government. We develop a two-link network simulation model with an untolled alternative to determine relative efficiency effects, and analyse rules for the government to organise the bidding process such that a more desired (welfare optimal) outcome is a! chieved. Our results show that, depending on the design of the auction, its outcomes may vary strongly, and may approach the maximum possible (second-best) welfare gains.
Keywords: 330; Traffic congestion; road pricing; private roads; second-best regulation; Straßenbau; Öffentlich-private Partnerschaft; Auktion; Straßenbenutzungsgebühr; Theorie